Satellite system integration based on Space Plug and Play Avionics - Kuwahara, T.; Yoshida, K.; Sakamoto, Y.; Tomioka, Y.; Fukuda, K. (2011 IEEE/SICE International Symposium on System Integration, 2011)
Professor Shinichi Nakasuka of University of Tokyo is now leading a small satellite development activity within the scope of a Japanese FIRST (Funding Program for World-Leading Innovative R&D on Science and Technology) program. In this program several 50 kg class microsatellites are going to be developed and launched by the end of Japanese fiscal year of 2013, including one scientific microsatellite under international cooperation. Tohoku University has been assigned as the project leader of this international scientific microsatellite named as RISESAT (Rapid International Scientific Experiment Satellite), and is developing the bus system as well as organizing scientific payload instruments from all over the world. This satellite shall demonstrate the performance of its bus system which is supposed to be offered as a common bus system for international scientific missions in the future. In order to accommodate a wide variety of payload instruments and to provide them flexible and comfortable integration environment, Space Plug and Play Avionics (SPA) standard is applied for the electrical interface between the payload instruments and the satellite bus system. The development of RISESAT flight model will be completed by the March 2013. This paper summarizes the system design of the satellite based on the SPA technology.